Família e cuidado domiciliar: “de cuidador a dependente” - Bruno, Tatiana de Fátima Domingues (2018)
This study is devoted to the examination of the triangular relationship between the ephemeral subject - here dependent on multiple care -, home care and family care. The management of this study considers that the relationship between the family and care-dependent persons does not take place in a single or homogeneous way, since it derives from a lot of social elements, economic, cultural, demographic and biological elements, based on the social and cultural historicity of its actual construction. These elements configure the objective and subjective conditions for the act of caring. The presence of the State is predominant, since it is responsible for guaranteeing the society's standards of civility, and the establishment of a relationship between the State and the family, based essentially on complementarity, not on the substitution of one or the other. Little submission of the family to the state. In order to identify the interfaces of protection and social deprotection in this process, the family's protective capacity, composed by the assessment of the objective conditions of the families, living territories and social ties, was used as the matrix. The qualitative research had as a locus the Home Care Service of the municipality of São Bernardo do Campo, called PID SBC and carried out the study of multiple cases through a home visit and interview. The complexity of the reality confronted by the families in care and, insofar as their protective capacity is concerned, reveals that the interactions between territory, links and objective conditions may reveal a tendency of the triangular relationship to present itself with more than one dependence be faced. The first one is due to the imperative biological condition of those who are ill, and the second concerns the social violations that the family caregivers are subjected to in this process